Weight, mortality, years of healthy life and active life expectancy in older adults - Diehr, Paula (2007)
OBJECTIVE: Two-thirds of older adults are currently classified as overweight or obese. Given that the importance of these weight categories was documented primarily in middle-aged persons, the survival and health status consequences for older adults are controversial. Here, we explore the issue of whether weight categories predict subsequent mortality and morbidity in older adults. DESIGN, SETTING, AND PARTICIPANTS: Data came from the Cardiovascular Health Study, a population-based cohort study of 5888 older adults. MEASUREMENTS: We estimated the age- and sex-specific probabilities of transition from one health state to another and from one weight category to another. From these probabilities we estimated future life expectancy, years of healthy life, active life expectancy, and the number of years spent in each weight and health category after age 65. RESULTS: Women who are healthy and of normal weight at age 65 have a life expectancy of 22.1 years. Of that, they spend, on average, 9.6 years as overweight or obese, and 5.3 years in fair or poor health. For both men and women, being underweight at age 65 was associated with worse outcomes than normal weight, while overweight and obesity were rarely worse than normal weight, and were sometimes associated with significantly better outcomes. CONCLUSIONS: Similar to middle-aged populations, older adults are likely to be or to become overweight or obese. However, higher weight is not associated with worse health in this age group. Thus, the number of older adults at a “healthy” weight may be much higher than currently believed.